Effect of Local Culture Based Learning in Science on Critical Thinking and Student Communication Skills - Hikmawati Hikmawati; Gunawan Gunawan; Haerunisyah Sahidu; Kosim Kosim (Journal of Science and Science Education, 2021)
Learning in every education unit in Indonesia is expected to develop good local cultural values so that it can make changes for the better in the future. In order to face future global competition, students at universities must have critical thinking and communication skills. This study aims to examine the effects of local culture-based learning in the field of Science on students' critical thinking and communication skills. The method used in this research is quantitative method with a posttest-only control group design. The subjects in this study were 58 students who attended the Study and Learning lectures at one of the universities in Mataram. Learning theories discussed through local culture-based learning for 8 meetings are behavioristic, cognitive, constructivist, and humanistic learning theories. The instruments used in this study were a test of critical thinking skills and an assessment sheet for student communication skills. Data analysis to test the research hypothesis using SPSS 25. The research showed that there were differences in critical thinking and communication skills between groups of students whose learning was based on local culture in the field of Science and groups of students whose learning was using conventional models. The level of critical thinking skills and communication skills in the group of students whose learning is based on local culture in the field of Science is higher when compared to the group of students whose learning uses conventional models